Accelerator programming using directives : 4th International Workshop, WACCPD 2017, Held in Conjunction with the International Conference for High Performance Computing, Networking, Storage and Analysis, SC 2017, Denver, CO, USA, November 13, 2017, Proceedings /: 4th International Workshop, WACCPD 2017, Held in Conjunction with the International Conference for High Performance Computing, Networking, Storage and Analysis, SC 2017, Denver, CO, USA, November 13, 2017, Proceedings. ([2018]) - Unknown
No abstract available